Strengthening Characteristics and Competence Entrepreneurship to Improve MSME Performance - Hidayat, Syamsul; Syiraf, M. Ilmi; Dwi Suseno, Bambang (AMCA Journal of Community Development, 2025)
Entrepreneurial characteristics and competencies are two important factors needed by entrepreneurs in Micro, Small, and Medium Enterprises (SMEs) to face the environmental challenges in the dynamic world of business and achieve high business performance. This study aimed to examine the effect of entrepreneurial characteristics and entrepreneurial competencies on SME performance. The study was conducted on SMEs in Serang, Banten, Indonesia. The research sample is 69 SMEs were determined through the purposive sampling method. Data were collected through a survey with questionnaires. Data were analyzed using structural equation modeling with Partial Least Square (PLS) approach. The results showed that entrepreneurial characteristics have a significant positive effect on entrepreneurial competencies, but entrepreneurial characteristics do have not a significant effect on the SME's performance and entrepreneurial competencies have a significant positive effect on the performance of SMEs. The results also indicate that entrepreneurial competence fully mediation the relationship between entrepreneurial characteristics and SMEs performance.